ENHANCING STUDENTS’ VOCABULARY KNOWLEDGE TROUGH READING THEMATIC STORY AT SMPN 6 WATAMPONE - Alfaraida Rumaisyah; Ishak Ishak; Wahyu Sultan (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study discusses reading thematic stories to increase students' vocabulary knowledge. This study used thematic stories as learning media. This study applied a pre-experimental method with a one group pre-test and post-test design. The population of this research is junior high school students from SMP Negeri 6 Watampone. The sample of this study consisted of 30 grade 7 students. This study used one instrument, namely the multiple-choice test. Data collection was carried out by conducting a pre-test and post-test to measure the development of students' vocabulary knowledge before and after treatment. As a result, it was revealed that there was a significant difference from the pre-test and post-test. The average pre-test score was 29.50 and the post-test average score was 79.83. From T-test the research found that the significant value (significant 2-tailed) value is lower than alpha (α) (0.000,05). It means that reading thematic story can improve students’ vocabulary knowledge.